Opera Batak Sampuraga: Penciptaan Seni Opera Batak - Enrico Alamo (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2018)
Opera Batak Sampuraga is a play that began from the experience of seeing a site Sampuraga Hot Water Pond, located in the area Sirambas Mandailing. and stories are told from the mouth to mouth (oral literatur). Then do the rearrangement of both characterizations and events that happen by using some structures of modern theater of Indonesia, because Batak Opera has some similarities with the structure of modern theater plays Indonesia. Opera Batak Sampuraga as the field of art creation, experiencing a touch of creativity include the presence of various elements of art from other regions. Sampuraga play is a human obsession and ambition in reaching goals, which requires sacrifice, although eventually a curse that will befall. Opera Batak similar expression pattern play in the play-the play is too modern Indonesian theater-style realism with representation approach is realized with the flowing fabric of conflict.